The relationship between crustacean diversity and population dynamics of Blood Cockle Tegillarca granosa in the coastal area of West Langsa, Aceh Province, Indonesia - MAWARDI MAWARDI; M. ALI SARONG; SUHENDRAYATNA SUHENDRAYATNA; MUHAMMAD IRHAM (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Mawardi, Sarong MA, Suhendrayatna, Irham M. 2024. The relationship between crustacean diversity and population dynamics of Blood Cockle Tegillarca granosa in the coastal area of West Langsa (Aceh Province, Indonesia). Biodiversitas 25: 690-699. Coastal areas serve as a transitional zone between land and sea, influenced by tidal fluctuations and river estuary currents. Coasts are ideal habitats for spawning and nurturing various crustaceans and bivalves. The aim of this study is to determine the relationship between the Shannon-Wiener diversity index of crustaceans and population dynamics of Tegillarca granosa (Linnaeus, 1758) (Arcidae, Bivalvia) in three different locations. The study utilized a survey method with sampling conducted using transects from the coastline towards the land in coastal areas covered with mangroves, employing transects measuring 5 meters by 5 meters. All samples collected at the study locations were fixed for identification. A total of 1,583 Crustacea individuals belonging to 17 species were sampled. The Shannon-Wiener diversity index of crustaceans ranged from 1.99 to 2.31, categorized as moderate. The highest number of individuals of T. granosa was in November, while the lowest number of individuals was recorded in July. Males of T. granosa were more dominant than females across all study sites. There was a positive correlation between the crustacean diversity index and T. granosa specimens, but a negative correlation with the crustacean dominance index. Seawater salinity, showed a positive correlation with crustacean diversity and the population dynamics of T. granosa.